Cardiac magnetic resonance analysis of left atrium function in patients with pre-apical hypertrophic cardiomyopathy - Wang, H.; Bo, K.; Gao, Y.; Zhou, Z.; Gao, X.; Sun, Zhonghua; Xu, L. (AME Publishing Company, 2024)
Background: Patients presenting with unexplained T wave inversion on electrocardiogram combined with thickened left ventricular apex but less than 15 mm had been proposed as a preclinical scope of apical hypertrophy cardiomyopathy (pre-ApHCM). However, analysis of left atrial (LA) function in these patients has not been studied. This study aims to evaluate the LA function in pre-ApHCM patients and compare it with patients with ApHCM using cardiac magnetic resonance (CMR) imaging.